Oracular consultation, fate and the concept of the individual - Eidinow, Esther (Franz Steiner Verlag, 2013)
This chapter examines the significance of the conception of the self for our understanding of the ritual practice of oracular consultation in ancient Greece, focusing primarily on the evidence of the question tablets from the sanctuary at Dodona, augmented by related literary material for oracular consultation.